1992
DOI: 10.1088/0264-9381/9/7/001
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic censorship violation in non-self-similar Tolman-Bondi models

Abstract: The occurrence of naked singularities in a class of non-self-similar Tolman-Bondi inhomogeneous dust collapse models is pointed out. These are shown to be strong curvature singularities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 10 publications
2
59
0
Order By: Relevance
“…One should note that departure from the homogeneous models by way of introducing arbitrarily small inhomogeneity does not necessarily make the singularity naked, as pointed out by our calculations here. This agrees with the earlier results such as those in [3,5,6].…”
supporting
confidence: 94%
See 1 more Smart Citation
“…One should note that departure from the homogeneous models by way of introducing arbitrarily small inhomogeneity does not necessarily make the singularity naked, as pointed out by our calculations here. This agrees with the earlier results such as those in [3,5,6].…”
supporting
confidence: 94%
“…An important subcase which could be examined in this context is the spherically symmetric but inhomogeneous distribution of dust which collapses under the force of gravity. The general solutions to Einstein equations for this case have been given by the Tolman-Bondi spacetimes [2], and it has been demonstrated that naked singularities can occur as the end state of such a collapse [3,4,5,6]. In particular, it was pointed out in [5,6] that the collapse ends in a naked singularity or a black hole depending on whether or not a certain algebraic equation involving the metric functions and their derivatives has positive real roots.…”
mentioning
confidence: 99%
“…Within this context, several gravitational collapse settings have been investigated over the past years which represent the occurrence of naked singularities. 3 Work along this line has been reported in the literature within a variety of models; among them we quote the role of inhomogeneities within the matter distribution on the final fate of gravitational collapse [12][13][14][15][16][17][18][19][20][21][22], collapse of a perfect fluid with heat conduction [23][24][25][26], the effects of shear on the collapse end-product [27][28][29][30], and the collapse process in the context of different gravitational theories [31,32] (see also [33,34] for recent reviews).…”
Section: Introductionmentioning
confidence: 99%
“…They have interestingly shown that for marginally bound case naked singularity is possible only upto five dimension while naked singularity may be possible in all dimensions for non marginally bound case. Then Goswami and Joshi [13] have pointed out that this peculiar feature of naked singularity (in marginal bound case) is due to the choice of the initial condition.In the present paper we study gravitational collapse for non-marginally bound case considering non self-similar solutions and it is generalization to higher dimension of the Dwivedi and Joshi [14]. The geodesic equations can not completely solved due to the presence of the complicated hypergeometric function.…”
mentioning
confidence: 99%
“…In the present paper we study gravitational collapse for non-marginally bound case considering non self-similar solutions and it is generalization to higher dimension of the Dwivedi and Joshi [14]. The geodesic equations can not completely solved due to the presence of the complicated hypergeometric function.…”
mentioning
confidence: 99%